Message from the Chairs QRS 2023 - W. Eric Wong; T.H. Tse; Suphamit Chittayasothorn; He Jiang (My University, 2023)
QRS 2023 - The 23rd IEEE International Conference on Software Quality, Reliability, and Security was held in-person for the first time in Chiang Mai, Thailand, from October 22 to 26 after three consecutive online virtual meetings from 2020 to 2022 due to the COVID-19 pandemic. Since some organizations still imposed certain constraints on international travel, the conference also allowed authors to give online presentations if they had appropriate justification.
Keywords: Information and Cyber Security; Web Application Security Vulnerabilities; Academic integrity and plagiarism